Coupled fixed point theorems for weakly compatible mappings along with CLR property in Menger metric spaces - Ben Aoua, L.; Aliouche, A. (Carpathian Mathematical Publications, 2016)
Coupled fixed point problems have attracted much attention in recent times. The aim of this paper is to extend the notions of E.A. property, CLR property and JCLR property for coupled mappings in Menger metric space and use this notions to generalizes the recent results of Jian-Zhong Xiao. The main result is supported by a suitable example.